2016
DOI: 10.1007/s00436-016-5070-x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic components of nervous system of Schistosoma mansoni and S. haematobium (Digenea: Schistosomatidae)

Abstract: A comparison has been made for the first time between the cholinergic components of the nervous system of important human digeneans namely Schistosoma mansoni and Schistosoma haematobium from infected hamster (Cricentus auratus) in Egypt. In each parasite, the central nervous system consists of two cerebral ganglia and three pairs of nerve cords (ventral, lateral, and dorsal) linked together by some transverse connectives and numerous ring commissures. Peripheral cholinergic innervation was detected in oral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that S. mansoni possesses a complex neurological and in vitro regeneration case, and nowadays there is still no functional study of Notch signaling involved in both [ 166 , 167 ].…”
Section: Functional Roles Of Notch Signaling Pathway Members In Inver...mentioning
confidence: 99%
“…Previous studies have shown that S. mansoni possesses a complex neurological and in vitro regeneration case, and nowadays there is still no functional study of Notch signaling involved in both [ 166 , 167 ].…”
Section: Functional Roles Of Notch Signaling Pathway Members In Inver...mentioning
confidence: 99%